Proceedings of the International Workshop Fission Dynamics of Atomic Clusters and Nuclei : Luso, Portugal, 15-19 May 2000 - Providência, João da (World Scientific, 2001)
In this volume, the main results of the last sixty years of research in nuclear fission are summarized, showing how ideas advanced from the beginning, for nuclei have also found useful applications in the new area of atomic clusters. The present status of the physics of fission is discussed in depth, and perspectives for further research are outlined. Contents: Fission Studies with Large Detector Arrays (J K Hwang et al.) Fission, Decay of Nuclei and the Extension of the Periodic System (W Greiner) Neutron Halo of Fissile Nuclei (V I Serov et.